Edukasi Kesehatan Pencegahan Stunting pada Ibu Hamil di Pulau Harapan Kepulauan Seribu, Jakarta - Nurbaeti, Irma; Rochanah, Siti; Yulianingsih, Yulianingsih; Idriani, Idriani; Kartini, Kartini (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2024)
Stunting is a condition in which children under the age of five fail to reach their proper height due to infections and chronic malnutrition. The incidence of stunting has been beginned since pregnancy. This is caused by insufficient nutritional intake during pregnancy, inappropriate diet, and low food quality. Lack of knowledge of mothers about health and nutrition before and during pregnancy has contribution. Therefore, it is important to carry out health education on stunting prevention for pregnant women. The purpose of community service was to provide knowledge to pregnant women about stunting prevention. The activity took place on Monday, July 24, 2023 at the Pulau Harapan Kepulauan Seribu, DKI Jakarta. A total of 20 pregnant women and 10 mothers of toddlers was participated. The methods beginned with a pretest, providing health education, and ending with a post-test. The results of education obtained an increase in knowledge score of 10.71, test results there was a significant increase (t-test = 4.177; p-value = 0.002). Conclusion. The importance of stunting prevention health education for pregnant women can be continued with healthy nutrition care programs and monitoring of pregnant women and toddlers, to prevent stunting.